Aplikasi SI-APIK Sebagai Solusi Penyusunan Laporan Keuangan bagi UMKM Makanan dan Minuman - Zuliyati Zuliyati; Wiwit Agus Triyanto; Hutomo Rusdianto (Muria Jurnal Layanan Masyarakat, 2023)
UMKM need to increase their productivity through technological improvements, so that the production process becomes more effective and efficient. Service partners are UMKM engaged in the food and beverage sector in Kudus Regency, namely Catering Bu Yati. The problem faced is the low management of the business and the unpreparedness of resources in the face of technological change so that the business is managed conventionally and traditionally. This service method uses technological guidance, application training and business management assistance. The output of this activity is the use of neat applications, increased income, as well as national seminars and publications through scientific articles in the form of proceedings or service journals.